THE ROLE OF AGROFORESTRY IN MAINTAINING BIODIVERSITY AND ECOSYSTEMS - Loso Judijanto (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Agroforestry, which combines agricultural practices with tree planting, plays a crucial role in maintaining biodiversity and ecosystem sustainability. This system creates diverse habitats and supports various species of flora and fauna, thus helping to increase biodiversity compared to monoculture farming. In addition, agroforestry supports ecosystem function by improving soil structure, controlling erosion, and maintaining soil fertility, as well as increasing water retention capacity. Trees in agroforestry also play a role in mitigating climate change through carbon sequestration, thereby reducing the greenhouse effect. By integrating nature conservation into agricultural practices, agroforestry offers a sustainable solution to global environmental challenges.